UPAYA MENINGKATKAN PEMAHAMAN KONSEP DAN AKTIVITAS BELAJAR MENGGUNAKAN MODEL JARING MAKANAN PADA SISWA KELAS VII SMPN 2 SANGGAU LEDO - Nofendra, Nofendra (Universitas Tanjungpura, 2019)
The teacher is a component of education that plays an important role in teaching and learning activities and is able to master learning in schools with models and methods that can make students understand the lessons given by the teacher. Therefore the 3D model carried out by the teacher knows the increase in understanding of concepts and learning activities about food webs as well as looking at students' responses to the food web model. The method used in this study uses the R D method to produce the following research data: Increased understanding of concepts 88%, increasing student learning activities on the criteria of learning activities is very high (29%) and high (59%) and student responses show high enthusiasm namely Strongly Agree (47%), Agree (37%), Doubtful (11%), Disagree (4%) and Strongly Disagree (2%).